2010
DOI: 10.1590/s0103-50532010001200009
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of triazenes: DNA cleavage, antibacterial activity and cytotoxicity against acute myeloid leukemia cells

Abstract: triazeno (3) foram avaliadas quanto à capacidade de clivagem do DNA plasmidial pUC18 e pBSKII, atividade antibacteriana e citotoxicidade in vitro frente a células de leucemia mielóide aguda e leucócitos normais utilizando o bioensaio da redução do sal brometo de 3-(4,5-dimetiltiazol-2-il)-2,5-difeniltetrazólio (MTT). Os triazenos analisados demonstraram capacidade de clivagem dos dois tipos de DNA plasmidial: triazeno 1 em pH 8,0 e 50 °C; triazeno 2 em pH 6,5 a 37 e 50 °C; triazeno 3 em pH 6,5 e 37 °C. Os comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Several studies using TZC compounds have shown that these compounds have broad antimicrobial activity (Hörner et al 2008;Domingues et al, 2010;Ombaka et al, 2012;Paraginski et al, 2014;Tizotti et al, 2016). Studies suggest that the antibacterial action of TZCs is due to the chelating activity of metal ions that are constituents of the bacteria cell wall, hindering their synthesis and leading to cell death (Hörner et al 2008;Ombaka et al, 2012).…”
Section: Biological Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies using TZC compounds have shown that these compounds have broad antimicrobial activity (Hörner et al 2008;Domingues et al, 2010;Ombaka et al, 2012;Paraginski et al, 2014;Tizotti et al, 2016). Studies suggest that the antibacterial action of TZCs is due to the chelating activity of metal ions that are constituents of the bacteria cell wall, hindering their synthesis and leading to cell death (Hörner et al 2008;Ombaka et al, 2012).…”
Section: Biological Activitymentioning
confidence: 99%
“…Barreiro et al (2012) reported that this metal acts inhibiting bacterial proliferation by blocking cell cytokinesis (Barreiro et al, 2012). Domingues et al (2010), obtained MIC values>128 mg/mL using TZCs not complexed with metal compounds against an S. epidermidis clinical isolate, as well as S. epidermidis ATCC 12128 strain (Domingues et al, 2010). In addition, another study using 15 TZC compounds not associated with metal showed MIC values=64 mg/mL for hospital isolates of S. epidermidis and S. saprophyticus (Horner et al, 2008).…”
Section: Biological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…These bacteria easily cause severe infection illness or food poisoning, and at the same time, they are widely applied to the antimicrobial activity screening experiments. [14][15][16][17] Analysis of the data in Table 2 showed that the compound 5l exhibited inhibitory activity against P. aeruginosa, K. pneumoniae, P. vulgaris, and S. typhimurium in the entire dose range of 8-256 nmol mL -1 , but was found to be inactive against P. multocida at even the highest concentration of 256 nmol mL -1 . The MIC of 5l against P. aeruginosa was found to be 8 nmol mL -1 , which was similar to that of the control ciprofloxacin, and lower than that of amoxicillin.…”
Section: 11mentioning
confidence: 99%
“…The geometrical parameters including bond length, bond angle and dihedral angles were presented in Table 1. Since the crystal structure of BBT is not available, the optimized structure was compared with other similar optimized compounds [26,27]. The molecule contains two CO-NH 2 groups and triazeno moiety with two benzene rings.…”
Section: The Geometrical Studiesmentioning
confidence: 99%